Ukuran Perusahaan Sebagai Variabel Pemoderasi Pengaruh Profitabilitas pada Penghindaran Pajak - Putra, Nyoman Trismana; Jati, I Ketut (E-Jurnal Akuntansi, 2018)
The purpose of this study is to determine the effect of profitability on tax avoidance with the firm sizeas a moderator variable. This research was conducted at manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange 2014-2016. The number of samples used in this study as many as 25 companies with 75 observations obtained with non-probability sampling technique with purposive sampling method. Data analysis technique is done by using analysis technique of moderated regression analysis. The results of the research show that profitability has a positive effect on tax avoidance. The study also found that firm size weakened the effect of profitability on tax avoidance. Keyword : profitability, firm size, tax avoidance